PERAN KOMUNITAS MAWAR MERAH DALAM PENGELOLAAN SAMPAH LIMBAH RUMAH TANGGA DI KELURAHAN TUGUREJO KECAMATAN TUGU KOTA SEMARANG - Suprihatiningsih; Fajar Ardiansyah (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
This study aims to find out how the participation and results of household waste management by the Mawar Merah community through the waste bank in Tugurejo Village. This study uses a qualitative method with a case study approach, the data obtained is through interviews, observation and documentation. The results of this study indicate that: (1) The role of the red rose community in waste management through waste banks is very large. This refers to 2 (two) roles, namely the role of coaching and the role of mentoring. (2) The results of waste management through the red rose community in the waste bank are organic waste (remaining vegetables, rotten fruits) with soil decomposing products (compost, MOL, and POC), then inorganic waste is made into works of art high selling value such as bags, chairs, flower vases, curtains etc.